Pengaruh Earning Per Share, Total Assets Turn Over dan Pertumbuhan Penjualan terhadap Harga Saham pada Perusahaan Sektor Property And Real Estate yang Terdaftar Di Bursa Efek Indonesia - Debora Silitonga; Putri Delima S.I Siregar; Rijal Siahaan; Andi Pranata Ginting; Rosmita Sari Siregar (COSTING : Journal of Economic, Business and Accounting, 2019)
The stock price is the price of a stock that occurs on the stock market, at a certain time determined by the market actor and determined by the demand and supply of the shares concerned in the capital market. This study aims to examine the effect of earnings per share, total asset turn over and sales growth on stock prices in the property and real estate sector companies listed on the Indonesia Stock Exchange (IDX). The population in this study was 47 companies and made a sample of 21 companies with purposive sampling technique. This study uses multiple linear regression analysis. The results of simultaneous research have an effect on stock prices. Partially earnings per share has a significant effect on stock prices, while total asset turnover and sales growth have no significant effect on stock prices. Simultaneously earnings per share, total assets turn over and sales growth have a significant effect on stock prices. Keywords: Earning Per Share, Total Assets Turn Over, Sales Growth, Stock Price